Pengelolaan Bantuan Dana Perimbangan Desa (Studi Kasus Di Desa Tapen Kecamatan Wanadadi Kabupaten Banjarnegara) - Astuti, Satria Dwi; Sunarto, Sunarto; Sumarno, Sumarno (Universitas Negeri Semarang, 2017)
Village financial management, should be based on openness to the public, especially in planing, implementing real based planing, administration in accordance wit the execution,by expenses or registration statements, the responsibilities based on the results of the report. Based on the results of observation, during the equalization fund management assistance Tapen village in the Village District of Banjarnegara district Wanadadi not yet fully public to know about the management of the balance funds help the village. Village goverment shouldbe more open to the public on the management of the village equalization grants. This research to what determine programs are financed with the assistance of village qualization funds, how community participation in the utilization of fund balance of the village, and how the use of funds balance accountability village. The research uses a qualitative approach. Data collection is done by using observation, interview, and documentation. The result showed that the villagers agreed programs include: construction of irrigation, construction of embankment, construction of drainage, rural community development program, and community empowerment program. Community participation in planning involving community and community leaders are to be included in the planning, white the authority given to the public to provide ideas/thoughts to determine development. In the implementation of community development activities did not participate because of the execution has been carried out by the builders. Public participation in the evaluation, the village goverment to convey the result of development or activities that have been implemented but the village government somestimes does not convey clearly the funds used in the activities carried out. Accountability mechanism support the use of eqalization fund account for thevillageis the chief financial accountability report to the regents through subdistric head.